Migrasi Internasional dan Politik Luar Negeri Indonesia - Elisabeth Dewi (Parahyangan Center for International Studies, 2013)
Many countries open up to capital flows and commodity as part of globalization. On the other hand, many countries are looking at migration, related to cultural differences, as a threat to sovereignty and national identity. In the context of international migration, Indonesia has a fairly complex position. Analysing the relationship between international migration and foreign policy, the two of Myron Weiner framework that we can use are the security / stability framework (SSF) and the international political economy framework (IPEF). In the end, based on that two frameworks can be seen that the migration process affects foreign policy goals and the other way, like two sides of coin. Both the framework can serve as the basis to think that both sending and receiving countries can take a significant opportunity.Keywords :globalization, international migration, foreign policy, domestic policy